Innate olfactory responses of female and male parasitoid Apanteles taragamae Viereck (Hymenoptera: Braconidae) toward host plant infested by the cucumber moth Diaphania indica Saunders (Lepidoptera: Crambidae). Issue 12 (2nd December 2017) - Nurkomar, Ihsan; Buchori, Damayanti; Taylor, DeMar; Kainoh, Yooichi
ABSTRACT: The behavioural responses of Apanteles taragamae, a larval parasitoid of the cucumber moth Diaphania indica, to the volatiles of cucumber plants was investigated in a four-arm olfactometer. Females and males were given a choice between several odour sources that included (1) clean air, (2) uninfested, (3) host-infested, and (4) mechanically damaged cucumber plants. Females and males showed different preferences for volatiles emanating from these plants. Females responded significantly longer to the volatiles from uninfested plants than clean air, and to host-infested plants than uninfested plants. There were no significant differences in female responses to the volatiles from mechanically damaged and uninfested plants . Males responded significantly longer to clean air rather than uninfested plants . The volatiles from both uninfested and host-infested cucumber plants may play important roles in host habitat location of A. taragamae females.